Upregulated Expression of MicroRNA-204-5p Leads to the Death of Dopaminergic Cells by Targeting DYRK1A-Mediated Apoptotic Signaling Cascade - Chiu, Ching-Chi; Yeh, Tu-Hsueh; Chen, Rou-Shayn; Chen, Hua-Chien; Huang, Ying-Zu; Weng, Yi-Hsin; Cheng, Yi-Chuan; Liu, Yu-Chuan; Cheng, Ann-Joy; Lu, Ya-Ching; Chen, Yu-Jie; Lin, Yan-Wei; et al. (Frontiers in Cellular Neuroscience, 2019)
MicroRNAs (miRs) downregulate or upregulate the mRNA level by binding to 3’-untranslated region (3’UTR) of target gene. Dysregulated miR levels can be used as biomarkers of Parkinson’s disease (PD) and could participate in the etiology of PD. In the present study, 45 brain-enriched microRNAs were evaluated in serum samples from 50 normal subjects and 50 sporadic PD patients. The level of miR-204-5p was upregulated in serum samples from PD patients. Upregulated level of miR-204-5p was also observed in the serum and SN of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mouse model of PD. Expression of miR-204-5p increased the level of α-synuclein (α-Syn), phospho-α-Syn, tau or phospho-tau protein and resulted in the activation of ER stress in SH-SY5Y dopaminergic cells. Expression of miR-204-5p caused autophagy impairment and activation of JNK-mediated apoptotic cascade in SH-SY5Y dopaminergic cells. Our study using bioinformatic method and dual-luciferase reporter analysis suggests that miR-204-5p positively regulates mRNA expression of dual-specificity tyrosine phosphorylation regulated kinase 1A (DYRK1A) by directly interacting with 3’UTR of DYRK1A. The mRNA and protein levels of DYRK1A were increased in SH-SY5Y dopaminergic cells expressing miR-204-5p and substantia nigra (SN) of MPTP- induced PD mouse model. Knockdown of DYRK1A expression attenuated miR-204-5p-induced increase in protein expression of phospho-α-Syn or phospho-tau, ER stress, autophagy impairment and activation of JNK-mediated apoptotic pathway. Our results suggest that upregulated expression of miR-204-5p leads to the death of dopaminergic cells by targeting DYRK1A-mediated ER stress and apoptotic signaling cascade.